Myocardial adenyl cyclase: activation by thyroid hormones and evidence for two adenyl cyclase systems - Levey, Gerald S. (1969)
The mechanism responsible for the hyperdynamic circulatory state in hyperthyroidism has not been defined. Although certain cardiac manifestations resemble those caused by excessive adrenergic stimulation, recent evidence suggests that thyroid hormone exerts an effect on the heart that is independent of the adrenergic system. Since the inotropic and chronotropic effects of norepinephrine appear to be mediated by activation of adenyl cyclase, the possibility that thyroxine and triiodothyronine are also capable of activating adenyl cyclase was examined in the particulate fraction of cat heart homogenates. L-thyroxine and L-triiodothyronine increased the conversion of adenosine triphosphate-(32)P (ATP-(32)P) to cyclic 3′,5′-adenosine monophosphate-(32)P (3′,5′-AMP-(32)P) by 60 and 45% respectively (P < 0.01). A variety of compounds structurally related to the thyroid hormones, but devoid of thyromimetic activity did not activate adenyl cyclase: these included 3,5-diiodo-L-thyronine, L-thyronine, 3,5-diiodotyrosine, monoiodotyrosine, and tyrosine. D-thyroxine activated adenyl cyclase and half maximal activity was identical to that of the L-isomer. Although the beta adrenergic blocking agent propranolol abolished norepinephrine-induced activation of adenyl cyclase, it failed to alter activation caused by thyroxine. When maximal concentrations of L-thyroxine (5 × 10(-6) moles/liter) and norepinephrine (5 × 10(-5) moles/liter) were incubated together, an additive effect on cyclic 3′,5′-AMP production resulted. This investigation demonstrates: (a) thyroid hormone is capable of activating myocardial adenyl cyclase in vitro and (b) this effect is not mediated by the beta adrenergic receptor. Moreover, the additive effects of norepinephrine and thyroxine suggest that at least two separate adenyl cyclase systems are present in the heart, one responsive to norepinephrine, the other to thyroid hormone. These findings are compatible with the hypothesis that the cardiac manifestations of the hyperthyroid state may, in part, be caused by the direct activation of myocardial adenyl cyclase by thyroid hormone.